Health Communication and Citizenship Among Sex Workers in Mysore, India: Beyond “Centers” and “Margins” - Khan, Shamshad; Lorway, Robert; O'Neil, John; Pasha, Akram; Reza-Paul, Sushena (Frontiers in Communication, 2019)
In the last couple of decades, there has been a significant turn towards critical and “culture-centered” approaches to health communication. Through the lens of critical ethnography, this paper aims to unsettle dominant Eurocentric and exclusionary notions of citizenship tied to a legislative and juridical framework of rights–as entitlements and obligations emanating from the “nation-state”. Instead, by focusing on the communicative practices of members of Ashodaya Samithi, a sex worker collective responding to local forms of discrimination and violence and susceptibility to the HIV infection, we disrupt dichotomous notions of political “centers” and “margins” by emphasizing how local forms of resistance and transnational alliance-building constitute complex socialities that enable sex workers to navigate risks, demand services, expand their rights and freedoms, while fulfilling individual and collective responsibilities. We argue that, in the “developing” world, emergent forms of citizenship are more likely to be found not in some concentrated center of cultural authority like the nation-state, or its ancillaries, but in more dispersed sites where postcolonial struggles may appear as uncivil, coarse, insurgent, impure, ambiguous, marginal, and thus threatening to more purified, populist portraits of nationhood redrawn by politicians and health officials. This paper highlights alternative voices often blocked by the dominant discourse, thereby potentially re-centring health communication in marginalized spaces. By juxtaposing field data and theory, this paper also aims to demonstrate how to engage in Critical Health Communication research with rigor and quality.